A deep-red-emission antimony(iii) chloride with dual-cations: extremely large Stokes shift due to high [SbCl6] distortion. Issue 100 (3rd December 2021) - Peng, Ying-Chen; Zhang, Zhi-Zhuan; Lin, Yang-Peng; Jin, Jian-Ce; Zhuang, Ting-Hui; Gong, Liao-Kuo; Wang, Ze-Ping; Du, Ke-Zhao; Huang, Xiao-Ying
Abstract : Presented is the first example of a [Sb(iii )Cl6 ]-based zero-dimensional metal halide with dual-organic-cations that shows deep-red emission with extremely large Stokes shift owing to high anion distortion. Abstract : Compound [C5 mim][Mim]2 [SbCl6 ] (1 ; [C5 mim] + = 1-pentyl-3-methylimidazolium; [Mim] + = N -methylimidazolium) with dual cations exhibits the first case of deep-red emission in [SbCl6 ] 3− -based 0D OIMHs. Anion distortion due to high disequilibrium of supramolecular interactions is revealed to be responsible for the extremely large Stokes shift of 335 nm and FWHM of 210 nm in the emission.